Pengaruh Mobile App Attractiveness, Functionality, Security dan Consumer Fulfillment Terhadap E-Loyalty dengan E-Satisfaction Sebagai Intervening pada E-Commerce Tokopedia - Krisnadi; Prima Mulyasari Agustini (MES Bogor, 2024)
With e-satisfaction serving as a mediator in the Tokopedia online business, the purpose of this study is to examine the impact of versatile application attractiveness, functionality, security, and customer fulfilment on e-loyalty. For the quantitative research approach, data were gathered through a survey. The members in this study are Tokopedia web based business clients who have made purchases there. The sample for this study is made up of some Tokopedia e-commerce customers who have purchased at least one mobile phone product since January 2023. Tokopedia is only available to customers in Greater Jakarta. In this study, probability sampling is used. The SEM-PLS approach is used by the specialist. The study found that attractiveness, security, and customer fulfillment of mobile apps had a significant impact on e-satisfaction. Functionality had no significant impact on e-satisfaction. E-loyalty is also significantly influenced by customer satisfaction and customer fulfillment. E-satisfaction had no significant impact on moderating customer fulfillment to e-loyalty in this study.